2011
DOI: 10.1088/1475-7516/2011/11/017
|View full text |Cite
|
Sign up to set email alerts
|

Light bending by nonlinear electrodynamics under strong electric and magnetic field

Abstract: We calculate the bending angles of light under the strong electric and magnetic fields by a charged black hole and a magnetized neutron star according to the nonlinear electrodynamics of Euler-Heisenberg interaction. The bending angle of light by the electric field of charged black hole is computed from geometric optics and a general formula is derived for light bending valid for any orientation of the magnetic dipole. The astronomical significance of the light bending by magnetic field of a neutron star is di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 36 publications
5
29
0
Order By: Relevance
“…Now let us consider the bending by a magnetic dipole 16 . Obviously, the bending by a magnetic dipole depends on the orientation of the dipole relative to the direction of the incoming ray.…”
Section: Bending By Magnetic Fieldmentioning
confidence: 99%
See 2 more Smart Citations
“…Now let us consider the bending by a magnetic dipole 16 . Obviously, the bending by a magnetic dipole depends on the orientation of the dipole relative to the direction of the incoming ray.…”
Section: Bending By Magnetic Fieldmentioning
confidence: 99%
“…The bending angle can be obtained by integration from the trajectory equation with y = b (impact parameter) and z = 0, which gives both horizontal (ϕ h = y (∞)) and vertical (ϕ v = z (∞)) deflections 16 ,…”
Section: Bending By Magnetic Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, to find the equations of the rays, we must integrate two second-order equations (13) and one first-order equation (14). The solution to these equations will contain five constants of integration, which can be uniquely identified using the five boundary conditions (11). We obtain…”
Section: Integrating the Differential Equations For Beams Of Electrommentioning
confidence: 99%
“…Experiments carried out at the Stanford Linear Accelerator Center (SLAC) [9] have shown that electrodynamics is a nonlinear theory even in a vacuum. Therefore, the study of the mathematical foundations of various nonlinear models of vacuum electrodynamics [10][11][12][13][14] is of interest for mathematical and theoretical physics.…”
Section: Introductionmentioning
confidence: 99%